THE SLOW DISCOVERY OF THE MACEDONIANS (Annual of the Faculty of Philosophy in Skopje, 2020)
The constant claim, even in the 21st century, that Macedonians are a nation inventedby the Comintern and Tito's Yugoslavia requires research to show that the formationof the Macedonian nation was not at all a solution of an international leftist organisation,but a natural process, similar as with other nations in the region. The proximityof the Macedonian with the Bulgarian language, and partly with the Serbian language,is not at all an argument for denying the existence of the Macedonian languageas a separate South Slavic language. At the end of the 19th and the beginning of the 20thcentury, the struggle led by the Macedonian Revolutionary Organisation for the creationof an autonomous Macedonian state aroused great interest among diplomats, politicians,journalists and intellectuals in Europe and the United States. As a result ofthat interest, many studies and pamphlets related to Macedonia and the possible solutionof the Macedonian issue emerged. While seemingly the theses of the sciences fromsome neighbouring countries are in their favour, careful researches show somethingquite opposite. Namely, many perceived that the Macedonian Slavic population wasneither Bulgarian nor Serbian, but separate South Slavic people appropriated by theneighbours. Moreover, in the United States, for example, where there was a right tofree expression of national feeling, some Macedonian emigrants declared themselves asthey felt, that is, as Macedonians.
Keywords: PEOPLE; LANGUAGE; MACEDONIAN SLAVS; MACEDONIANS